New combinations in Persicaria (Polygonaceae: Persicarieae) for the Flora of China - Li, Bo; Fan, Dengmei; Lei, Shuqing; Zhang, Zhiyong (Phytotaxa, 2013)
The generic delimitation of Polygonum Linnaeus (1753: 359) has been controversial, and interpreted differently by various authors, especially in the past (Meisner 1826, Gross 1913, Tzvelev 1987). Several morphological and anatomical characters, such as in pollen (Hedberg 1946), vegetative parts (Haraldson, 1978), flower (Ronse Decraene & Akeroyd 1988), and fruit (Ronse Decraene et al. 2000), have been considered in subdividing the heterogeneous genus Polygonum into a number of smaller groups, which was also supported by recent molecular studies (Sanchez et al. 2009, Sanchez et al. 2011, Schuster et al. 2011). Genera and tribes in the buckwheat family have been redefined (Sanchez et al. 2011) and Persicaria(Linnaeus 1753: 360) Miller (1754), which is formerly and popularly treated as synonym of Polygonum in tribe Polygoneae, has been placed in the redefined tribe Persicarieae (Sanchez et al. 2011). Many combinations were already proposed to accommodate these generic changes, but six Polygonum species in the Flora of China (Li et al. 2003), have not been transferred and the new combinations in Persicaria are still necessary. Information on the types (five holotypes and one lectotype here designated) and morphological notes are also provided.